A rare earth-free GaZnON phosphor prepared by combustion for white light-emitting diodes. Issue 7 (27th January 2015) - Chouhan, Neelu; Lin, Chun Che; Hu, Shu-Fen; Liu, Ru-Shi
Abstract : Rare earth-free phosphor GaZnON was synthesized by combustion of a unimolar mixture of metal oxides and urea, which can be used in WLEDs. Abstract : Nanophosphor GaZnON was synthesized by combustion using a unimolar mixture of metal oxides and urea as a flux/combustible agent at varying temperature and time; the resulting products crystallized in a single monoclinic phase and had broad PLE spectra (300–550 nm at λ ex = 350 nm) with the characteristic blue emission that can be utilised in white light-emitting diodes by adding them with red and green light-emitting phosphors and by using a UV LED ( λ ex = 300 nm). Phosphors were examined according to respective package parameters. The blue light-emitting phosphor GaZnON was found to have excellent potential in white light-emitting diode devices by assimilating them with already viable red and green light-emitting phosphors and by stimulating them using a near-UV LED chip with wavelength λ ex = 300 nm. The possible electron transition mechanism responsible for the luminescence process is also discussed based on the experimental data.